Disrupted Routine Medical Visits in Children and Adolescents During the COVID-19 Pandemic, January-June 2021 - Samira M. Badeh, BS; Laurie D. Elam-Evans, PhD, MPH; Holly A. Hill, MD, PhD; Benjamin Fredua, MS (Elsevier, 2023)
Introduction: Recent studies have indicated the COVID-19 pandemic has disrupted routine vaccinations. This study describes the prevalence and characteristics of children and adolescents experiencing disrupted routine vaccination and other medical visits in the U.S. between January and June 2021. Methods: The National Immunization Surveys were the source of data for this cross-sectional analysis (n=86,893). Parents/guardians of children aged between 6 months and 17 years were identified through random-digit dialing of cellular phone numbers and interviewed. Disrupted visits were assessed by asking: In the last 2 months, was a medical checkup, well-child visit, or vaccination appointment for the child delayed, missed, or not scheduled for any reason? Respondents answering yes were asked: Was it because of COVID-19? Sociodemographic characteristics of children/adolescents with (1) COVID-19-related missed visits and (2) non-COVID-19-related missed visits were examined. Statistical differences within demographic subgroups were determined using t-tests, with p-values <0.05 considered statistically significant. Linear regression models were used to examine the trends in disrupted visits over time. Results: An estimated 7.9% of children/adolescents had a missed visit attributed to COVID-19; 5.2% had a missed visit that was not COVID-19-related. Among children/adolescents with a COVID-19-related missed visit, a higher percentage were of minority race or ethnicity, lived below the poverty level, had a mother without a college degree, and lived in the western U.S. There was a significant decline in the COVID-19-related missed visits over time. Conclusions: COVID-19 disrupted routine vaccination or other medical visits inequitably. Catch-up immunizations are essential for achieving adequate vaccination of all children/adolescents.